Mushtāq Aḥmad Yūsufī kī adabī ḵẖidmāt - Ṭāhir, Muạmmad (Aʻẓamgaṛh : Muḥammad T̤āhir, 2003)
On the works of Mushtāq Aḥmad Yūsufī, Urdu satirist.
Includes bibliographical references (p. 243-246).
Mode of access: Internet.
In Urdu.
Keywords: Yūsufī, Mushtāq Aḥmad, -- 1923-2018 -- Criticism and interpretation